Rare Case of Left Ventricular Thrombus Postmyocardial Infarction for Emergency Decompressive Craniectomy - Arikrishnan, Thirumurugan; Chakravarthy, Deepak; Uthaman, Duraiyarassu; Srinivasan, Gnanasekaran (Journal of Neuroanaesthesiology and Critical Care, 2021)
Left ventricular (LV) thrombus formation is a notorious complication encountered in postmyocardial infarction patients. Such cases, when coming for noncardiac surgery, put the patient at greater risk of embolic events. Anesthesiologists play a pivotal role in the management of such rare and difficult cases. There is sparse evidence on management of such cases for noncardiac surgery. Hence, we would like to share our experience of a young patient with LV thrombus posted for left decompressive craniectomy.
Keywords: craniectomy; left ventricular thrombus; myocardial infarction